Digitizing food experience: Food taste perception on digital image and true form using hashtags - Afdallyna Fathiyah Harun; Norhafiza Ruslan; Wan Adilah Wan Adnan; Saiful Izwan Suliman; Juhaida Ismail; Hanif Baharin (Institute of Advanced Engineering and Science, 2020)
Food experience is now omnipresent with the increased use of social media such as Instagram. Users often share food images or video which is often accompanied with #hashtags. Readers of the post are required to tap into their visual cognition and perception of what it represents. Little exploration has been done to understand if image can simulate food taste and how similar is the perception after user tasted the food. We were motivated to understand the difference of food taste perception on digital image and its true form by studying user hashtags. We applied the case study approach where we focused on a Malaysian dessert to compare user perception of the cakes’ dimension which are appearance, flavour, texture and hedonic. Using Instagram, users were requested to create hashtags that depict their taste perception of the cakes before and after tasting the cake. The hashtags were then analysed using content analysis where we found that the perception on digital image and true form had a degree of difference where many of the initial perception were inaccurate. This implies that visual images may not be able to facilitate accurate food taste perception and would need further technology interactivity to achieve the objective.